PENERAPAN METODE IMPLICIT RATING UNTUK SISTEM REKOMENDASI RESEP MASAKAN BERBASIS MOBILE WEB - Inri Christiana Winardy; Mohammad Fajar; m (KHARISMA Tech, 2018)
The purpose of this research is to apply and evaluate the recipe recommendation system using implicit rating method that can help the user to choose the recipe that correspond to that user. The implicit rating indicator used is a repeat visits. Data collection in this study was conducted through literature studies, questionnaires, and testing of web-based applications developed. To get recommendations, users are already registered and make multiple visits to multiple recipes. Implemented using Codeigniter Framework with PHP programming language. This study used 68 recipes and 8 respondents as users. From the results of the study, all of the respondents received a recommendation. A trial is conducted to find out how many recommendations are appropriate for the user. The result obtained is the average percentage corresponding to the user that is 69.7625%, while the average percentage incompatibility with the user is 30.2375%.